Defining Arthritis for Public Health Surveillance: Methods and Estimates in Four US Population Health Surveys. Issue 3 (March 2017) - Murphy, Louise B.; Cisternas, Miriam G.; Greenlund, Kurt J.; Giles, Wayne; Hannan, Casey; Helmick, Charles G.
Abstract : Objective: To determine the variability of arthritis prevalence in 4 US population health surveys. Methods: We estimated annualized arthritis prevalence in 2011–2012, among adults age ≥20 years, using 2 definition methods, both based on self‐report: 1) doctor‐/health care provider–diagnosed arthritis in the Behavioral Risk Factor Surveillance Survey (BRFSS), National Health and Nutrition Examination Survey (NHANES), National Health Interview Survey (NHIS), and Medical Expenditure Panel Survey (MEPS); and 2) three arthritis definitions based on International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) criteria in MEPS (National Arthritis Data Workgroup on Arthritis and Other Rheumatic Conditions [NADW‐AORC], Clinical Classifications Software [CCS], and Centers for Disease Control and Prevention [CDC]). Results: Diagnosed arthritis prevalence percentages using the surveys were within 3 points of one another (BRFSS 26.2% [99% confidence interval (99% CI) 26.0–26.4], MEPS 26.1% [99% CI 25.0–27.2], NHIS 23.5% [99% CI 22.9–24.1], NHANES 23.0% [99% CI 19.2–26.8]), and those using ICD‐9‐CM were within 5 percentage points of one another (CCS 25.8% [99% CI 24.6–27.1]; CDC 28.3% [99% CI 27.0–29.6]; and NADW‐AORC 30.7% [99% CI 29.4–32.1]). The variation in the estimated number (in millions) affected with diagnosed arthritis was 7.8 (BRFSS 58.5 [99% CI 58.1–59.1], MEPS 59.3 [99% CI 55.6–63.1], NHANES 51.5 [99% CI 37.2–65.5], and NHIS 52.6 [99% CI 50.9–54.4]), and using ICD‐9‐CM definitions it was 11.1 (CCS 58.7 [99% CI 54.5–62.9], CDC 64.3 [99% CI 59.9–68.6], and NADW 69.9 [99% CI 65.2–74.5]). Most (57–70%) reporting diagnosed arthritis also reported ICD‐9‐CM arthritis; respondents reporting diagnosed arthritis were older than those meeting ICD‐9‐CM definitions. Proxy response status affected arthritis prevalence differently across surveys. Conclusion: Public health practitioners and decision makers are frequently charged with choosing a single number to represent arthritis prevalence in the US population. We encourage them to consider the surveys' purpose, design, measurement methods, and statistical precision when choosing an estimate.